Comparing clinical acne vulgaris severity to adolescent and parent perceptions of acne severity and impact on quality of life. Issue 4 (27th May 2020) - Sadowsky, Lauren M.; Yang, Connie Y.; Sorrell, Jennifer; Bayers, Stephanie; O'Neill, Lauren B.; Chamlin, Sarah L.; Schlosser, Bethanee J.
Abstract: Background/Objectives: Little research has compared clinician acne severity assessment with either adolescent‐ or parent‐rated scales of acne severity or impact on quality of life (QOL). We sought to assess how adolescents and their parents perceive the severity and impact of acne on the adolescent's QOL and correlate this with clinical severity. Methods: Each adolescent and a parent completed a validated QOL survey regarding the adolescent's acne and rated the adolescent's acne severity and QOL impact using a Likert scale. Clinicians assessed the adolescent's acne using a standardized acne severity scale. Statistical analysis compared adolescent scores with respective parent scores or with clinician assessment using a paired t test or Spearman rank‐order correlation test. Results: The Likert impact score more accurately reflected acne impact on QOL for adolescents than for parents when considering the validated QOL survey as the gold standard ( r 2  = .56 vs r 2  = .36). Likert scores for adolescents and parents were weakly correlated for acne severity but not for acne QOL impact ( r 2  = .36 vs r 2  = .18). Correlations of acne severity scores between clinician and either adolescent or parent were weak. Conclusions: Parents and adolescents are in relative agreement regarding acne severity and QOL impact. However, parent and adolescent perceptions are disparate from clinician acne assessment. It is important that physicians identify and consider adolescent and parent perceptions in addition to clinical assessment to better inform the approach to acne management.